Trends in laboratory-confirmed bacterial meningitis (2012–2019): national observational study, EnglandResearch in context - Sathyavani Subbarao; Sonia Ribeiro; Helen Campbell; Ifeanyichukwu Okike; Mary E. Ramsay; Shamez N. Ladhani (The Lancet Regional Health. Europe, 2023)
Summary: Background: Bacterial meningitis is associated with significant morbidity and mortality worldwide. We aimed to describe the epidemiology, aetiology, trends over time and outcomes of laboratory-confirmed bacterial meningitis in England during 2012–2019. Methods: UK Health Security Agency routinely receives electronic notifications of confirmed infections from National Health Service hospital laboratories in England. Data were extracted for positive bacterial cultures, PCR-positive results for Neisseria meningitidis or Streptococcus pneumoniae from cerebrospinal fluid and positive blood cultures in patients with clinical meningitis. Findings: During 2012–19, there were 6554 laboratory-confirmed cases. Mean annual incidence was 1.49/100,000, which remained stable throughout the surveillance period (p = 0.745). There were 155 different bacterial species identified, including 68.4% (106/1550) Gram-negative and 31.6% (49/155) Gram-positive bacteria. After excluding coagulase-negative staphylococci (2481/6554, 37.9%), the main pathogens causing meningitis were Streptococcus pneumoniae (811/4073, 19.9%), Neisseria meningitidis (497/4073, 12.2%), Staphylococcus aureus (467/4073, 11.5%), Escherichia coli (314/4073, 7.7%) and group B streptococcus (268/4073, 6.6%). Pneumococcal meningitis incidence increased significantly during 2012–9, while meningococcal, group A streptococcal and tuberculous meningitis declined. Infants aged <3 months had the highest mean incidence (55.6/100,000; 95% CI, 47.7–63.5) driven mainly by group B streptococci, followed by 3–11 month-olds (8.1/100,000; 95% CI 7.1–9.0), where pneumococcal and meningitis predominated. The 30-day case-fatality rate (CFR) was 10.0% (71/6554). Group A streptococcal meningitis had the highest CFR (47/85, 55.3%). The probability of surviving at 30 days was 95.3% (95% CI, 93.4–97.3%) for infants and 80.0% for older adults (77–84%). Interpretation: The incidence of bacterial meningitis has remained stable. The high CFR highlights a need for prevention through vaccination. Funding: PHE.